(untitled) (Journal of Event, Tourism and Hospitality Studies, 2025)
With the global coffee trend fostering growth in coffee-related businesses, understanding these elements such as food quality, service quality, and contextual experience are crucial for sustaining customer loyalty and business competitiveness. This study investigates the factors influencing consumers’ revisit intentions to coffee houses in Penang, focusing on food quality, service quality, and contextual experience. The research aims to provide insights for coffee house businesses to enhance customer retention and thrive in a competitive market. The research employs a quantitative approach, analyzing responses from 100 online questionnaires distributed between January and March 2022. The study focuses on three main variables: food quality, service quality, and contextual experience. The study employs descriptive and inferential analyses, specifically Pearson correlation and regression analysis, to examine the relationships between food quality, service quality, contextual experience, and revisit intentions. Findings suggest that high food quality, excellent service, and positive contextual experiences significantly enhance consumers’ likelihood to revisit. Furthermore, contextual experience emerges as the most critical factor, significantly influencing consumer revisit intention. The findings reveal that food quality does not significantly influence revisit intentions (p > 0.05), indicating its limited role compared to other factors. In contrast, service quality and contextual experience significantly predict revisit intentions, with contextual experience emerging as the strongest predictor. These insights are crucial for coffee house owners to enhance customer satisfaction and loyalty. The results contribute to a deeper understanding of consumer behavior in the context of Penang’s thriving coffee culture.